(untitled) (Mustansiria Dental Journal, 2018)
Diabetes mellitus is a major global health problem and represents a risk factor for periodontitis. This study was carried out to determine the Paraoxonase (PON), adenosine deaminase (ADA), aspartate and alanine aminotransferase (AST, ALT), lactate dehydrogenase (LDH) activity in diabetic patients with Periodontitis. This study was carried out on nineteen diabetic patients (25–50 years),) with generalized moderate-to-severe periodontitis were selected based on periodontal parameters of gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL) and radiographic parameters. As well as 19 healthy agematched control participants. Data were evaluated using descriptive statistics, ttest, Chi-Square. Results: Obtained results were shown statistically significant increases of activity of ADA, LDH, AST, and ALT, while PON concentration decreased in saliva from diabetic patients with periodontal disease in relation to control group. Conclusion: In patients with advanced periodontitis, the salivary PON, level were significantly lower whereas ADA higher compared to healthy individuals. Thus, assessment of salivary leptin can be done as a non-invasive and simple method to determine the susceptibility of patients to advanced periodontitis.